The Lake Shore Electric Railway story - Harwood, Herbert H., Jr; Korach, Robert S. (Railroads past and present., 2016)
"Here is the fully illustrated story of "The Greatest Electric Railway in the United States," which connected the Lake Erie cities of Toledo and Cleveland. Before its untimely death in 1938, it left a rich legacy of bold innovation and imaginative marketing practices"--Back cover